Remarks on ecological awareness - Klimski, Marcin (Studia Ecologiae et Bioethicae, 2007)
Forming ecological awareness of children, young people and adults is one of the most important challenges of the contemporary world. This process is of great importance, as it leads to forming a pro-ecological behaviour, resulting in proper attitudes of people to the environment. This article shows the ways of understanding ecological attitude. We consider its wide versus narrow meaning. We also present types of ecological attitudes and the values belonging to its development and to making it work in everyday live.